Analisis Sentimen Komentar Pengguna Mobile JKN di Google Play Store - Moh. Ilham Ramdhan; Muhammad Iqbal Nurdiansyah; Nadia Nur Amalia (UIN Sunan Gunung Djati Bandung, 2024)
The government continues to strive to improve the quality of public health through the social security system. One of them is launching the Mobile JKN health service application, which with one hand the government can make it easier for the public to access good health information and services. However, in the implementation of the Mobile JKN application there are many obstacles when accessed by users, therefore research was carried out with the aim of seeing public satisfaction regarding the health services provided by the government through the JKN mobile application. Researchers used qualitative research methods with a literature study approach. The research results prove that the government still has to evaluate and improve the Mobile JKN application in an effort to optimize Mobile JKN services, this is because users who give negative reviews dominate all reviews compared to users who give positive reviews, which means that people's needs have not been met. On the other hand, some people feel the benefits of the Mobile JKN application because it can save time and energy.